Optimalisasi Fungsi Kognitif Anak Tunagrahita Melalui Layanan Bimbingan Kelompok Berbasis Permainan Edukatif - Fitria Ariani; Nur Syahadani Putri; Rosi Kumala Sari (LPPM Universitas Dharma Andalas, 2026)
This Community Service (PKM) activity aims to optimize the cognitive function of children with intellectual disabilities through educational game-based group guidance and counseling (BK) services. The activity was implemented in the form of group guidance services using various educational games such as matching games, memory games, sorting games, and sequencing games. The activity was evaluated using pre-test and post-test methods for concentration, memory, and simple logic. The results of the activity showed an improvement in the cognitive function of children with intellectual disabilities. Concentration increased from 52% to 81%, memory increased from 48% to 78%, and simple logic increased from 45% to 74%. Concentration, memory, and basic logic improved during the activity. This activity demonstrates that educational game-based group guidance can improve the cognitive function of children with intellectual disabilities and is expected to become an innovative, applicable, and sustainable model for BK services for children with intellectual disabilities.